Drosophila pericentrin requires interaction with calmodulin for its function at centrosomes and neuronal basal bodies but not at sperm basal bodies. - Galletta, B.J.; Guillen, R.X.; Fagerstrom, C.J.; Brownlee, C.W.; Lerit, D.A.; Megraw, T.L.; Rogers, G.C.; Rusan, N.M. (Molecular Biology of the Cell, 2014)
Pericentrin is a critical centrosomal protein required for organizing pericentriolar material (PCM) in mitosis. Mutations in pericentrin cause the human genetic disorder Majewski/microcephalic osteodysplastic primordial dwarfism type II, making a detailed understanding of its regulation extremely important. Germaine to pericentrin's function in organizing PCM is its ability to localize to the centrosome through the conserved C-terminal PACT domain. Here we use Drosophila pericentrin-like-protein (PLP) to understand how the PACT domain is regulated. We show that the interaction of PLP with calmodulin (CaM) at two highly conserved CaM-binding sites in the PACT domain controls the proper targeting of PLP to the centrosome. Disrupting the PLP-CaM interaction with single point mutations renders PLP inefficient in localizing to centrioles in cultured S2 cells and Drosophila neuroblasts. Although levels of PCM are unaffected, it is highly disorganized. We also demonstrate that basal body formation in the male testes and the production of functional sperm does not rely on the PLP-CaM interaction, whereas production of functional mechanosensory neurons does.